IMPLEMENTASI STRATEGI PEMBELAJARAN MEMBACA DAN BERCERITA DI LEMBAGA PENDIDIKAN TK (TAMAN KANAK-KANAK) - M As`ad Nahdly (MIYAH : Jurnal Studi Islam, 2017)
This article explains about the implementation of reading and telling learning strategies in kindergartens. So far we know that learning is the main aspect in the education process, because the learning experience that students get during the learning process will play a very important role in the formation of abilities which will then determine the quality of education. In the activities of the teaching and learning process, the learning strategy has a very important role, one of which is the application of learning strategies to reading and telling stories. The main discussion in this article explains the Implementation of Reading Learning Strategies and Tells Stories at Kindergarten (Kindergarten) Institutions. This article is a conceptual description taken in depth from various book references and information from various sources. Analysis obtained is that reading activities must be carried out if the child is happy, so that the child will be able to enjoy and digest what they are reading, namely through the world of games or singing..Keywords:Â  learning strategies, reading and telling